Signs and signals limiting myocardial damage using PICSO: a scoping review decoding paradigm shifts toward a new encounter - Mohl, Werner; Kiseleva, Zlata; Jusic, Alem; Bruckner, Matthäus; Mader, Robert M. (Frontiers in Cardiovascular Medicine, 2023)
Background Inducing recovery in myocardial ischemia is limited to a timely reopening of infarct vessels and clearing the cardiac microcirculation, but additional molecular factors may impact recovery. Objective In this scoping review, we identify the paradigm shifts decoding the branching points of experimental and clinical evidence of pressure-controlled intermittent coronary sinus occlusion (PICSO), focusing on myocardial salvage and molecular implications on infarct healing and repair. Design The reporting of evidence was structured chronologically, describing the evolution of the concept from mainstream research to core findings dictating a paradigm change. All data reported in this scoping review are based on published data, but new evaluations are also included. Results Previous findings relate hemodynamic PICSO effects clearing reperfused microcirculation to myocardial salvage. The activation of venous endothelium opened a new avenue for understanding PICSO. A flow-sensitive signaling molecule, miR-145-5p, showed a five-fold increase in porcine myocardium subjected to PICSO. Verifying our theory of “embryonic recall,” an upregulation of miR-19b and miR-101 significantly correlates to the time of pressure increase in cardiac veins during PICSO (r2 = 0.90, p < 0.05; r2 = 0.98, p < 0.03), suggesting a flow- and pressure-dependent secretion of signaling molecules into the coronary circulation. Furthermore, cardiomyocyte proliferation by miR-19b and the protective role of miR-101 against remodeling show another potential interaction of PICSO in myocardial healing. Conclusion Molecular signaling during PICSO may contribute to retroperfusion toward deprived myocardium and clearing the reperfused cardiac microcirculation. A burst of specific miRNA reiterating embryonic molecular pathways may play a role in targeting myocardial jeopardy and will be an essential therapeutic contribution in limiting infarcts in recovering patients.